2016
DOI: 10.1371/journal.pone.0166316
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Stromal Cells-Induced Neural Differentiation of Mouse Embryonic Stem Cells

Abstract: Deriving specific neural cells from embryonic stem cells (ESCs) is a promising approach for cell replacement therapies of neurodegenerative diseases. When co-cultured with certain stromal cells, mouse ESCs (mESCs) differentiate efficiently to neural cells. In this study, a comprehensive gene and protein expression analysis of differentiating mESCs is performed over a two-week culture period to track temporal progression of cells from a pluripotent state to specific terminally-differentiated neural cells such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…28,37 Persistent and increasing gene expression of these factors in differentiating mESCs is consistent with their roles in development of specific neural cells that takes place during the second week of co-culture of mESCs and PA6 cells. 38,39 In summary, the fold change data in Fig 5a–b suggests that a group of 12 factors self-regulate neural cell differentiation of mESCs in this co-culture system.…”
Section: Resultsmentioning
confidence: 73%
“…28,37 Persistent and increasing gene expression of these factors in differentiating mESCs is consistent with their roles in development of specific neural cells that takes place during the second week of co-culture of mESCs and PA6 cells. 38,39 In summary, the fold change data in Fig 5a–b suggests that a group of 12 factors self-regulate neural cell differentiation of mESCs in this co-culture system.…”
Section: Resultsmentioning
confidence: 73%
“…Copyright 2017, Oxford University Press. c) Reproduced with permission . Copyright 2016, Public Library of Science.…”
Section: Applications: Toward Functional Artificial Llpsmentioning
confidence: 99%
“…Proliferation of pluripotent mESCs and resulting multipotent neural stem and progenitor cells causes growth and formation of the colonies during the first week of culture. Cells subsequently acquire less proliferative neuronal or glial progenitor states or terminally differentiate to neurons, astrocytes, or oligodendrocytes during the second week (Joshi, Buchanan, Paruchuri, Morris, & Tavana, ; Kawasaki et al, ). Our temporal gene expression study showed transition in the state of mESCs and supported this explanation (Figure S1–S3).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that expression of specific markers of neural stem and progenitor cells, such as Nestin and TuJ, and neurite processes is detectable in mESCs colonies starting from the fourth day of coculture with PA6 cells (Joshi et al, ). The expression of neural markers gradually increased until Day 8 and plateaued thereafter.…”
Section: Resultsmentioning
confidence: 99%